2023
DOI: 10.3390/ijfs11010035
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between Macroeconomic Factors and Corporate Investment: Empirical Evidence from GCC Markets

Abstract: The current study aims to explore the role of various macroeconomic factors in determining corporate investment. Using firm-level data of six Gulf Cooperation Council (GCC) region countries for a 14 year period (2007–2020), the current study establishes the empirical analysis by employing the system generalized method of moments (GMM) technique. The empirical results reveal the negative impact of foreign direct investment whilst the positive impact of economic growth, financial development, and inflation rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The process of industrialization plays an essential role in promoting the economy from recession to prosperity and moving it from underdevelopment to development. Industrial businesses make financial decisions that are more susceptible to changes in the overall economy (Umar Farooq et al, 2023). The industrial and food sectors are the most critical and variables that impact all economic sectors, the activity of the industrial sector must be guided by a clearly defined strategy that ensures that the potential effects of economic variables are contained and their adverse effects reduced (Mohammed, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of industrialization plays an essential role in promoting the economy from recession to prosperity and moving it from underdevelopment to development. Industrial businesses make financial decisions that are more susceptible to changes in the overall economy (Umar Farooq et al, 2023). The industrial and food sectors are the most critical and variables that impact all economic sectors, the activity of the industrial sector must be guided by a clearly defined strategy that ensures that the potential effects of economic variables are contained and their adverse effects reduced (Mohammed, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the commodity sectors have paid attention to their ability to generate income, create employment and achieve sectoral linkages. Their contribution to the diversification and expansion of the productive base thus helps to reduce dependence on the import of goods from abroad, thereby reducing the trade deficit and It should be noted that economic performance, particularly in the manufacturing sector, in 2010 has been affected by the global financial crisis over the past several years, with the growth rate in the manufacturing sector in 2008, 2009, and 2010(3.2, 2.6 and 13.4), respectively (Central Bank, 2014. In addition to events in neighboring countries, Jordan still suffers from their economic impact.…”
Section: Introductionmentioning
confidence: 99%
“…Farooq et al (2020) analysed the economic relationship between different macroeconomic factors and corporate investment decision in 12 selected Asian countries over the period 2007–2016. Farooq et al (2023) also explored the role of macroeconomic factors in determining corporate investment for six members of Gulf Cooperation Council region countries over the period 2007–2020. They found that economic growth, financial development and inflation rate positively drive the investment by enhancing the demand for industrial products, cheap financing and price appreciation effect on production.…”
Section: Introductionmentioning
confidence: 99%